Rancang Bangun Sistem Informasi Pariwisata Di Kabupaten Musi Rawas Utara Provinsi Sumatera Selatan - Muhammad Zarkasi; Khairil Khairil; Achmad Fikri Sallaby (UNIVED Press, 2024)
Tourism is a journey that a person undertakes temporarily from one place to another for the purpose of recreation, holidays and enjoying tourist attractions, not with the intention of earning a living in the place he or she visits but solely to enjoy leisure or recreational activities to fulfill various desires. .The stages of research based on the waterfall method are as follows: Analysis, Design, coding, Implementation, Maintenance, from the results of creating a Web-Based Tourism Information System Design System in the North Musi Rawas Regency, South Sumatra Province, the conclusion is: System Design System Tourism information in North Musi Rawas Regency, South Sumatra Province is used as a tool in conveying tourism information in North Musi Rawas Regency. The Tourism Information System. The design of a tourism information system. In North Musi Rawas Regency, South Sumatra Province, it is one form of tourism promotion that exists. in North Musi Rawas Regency to attract tourists to visit